Mapping the intellectual and conceptual structure of physical education research: Direct citation analysis - Andrzej Lis; Mateusz Tomanek (Physical Education of Students)
Background and Study Aim. The aim of the study is to identify and explore the intellectual and conceptual structure of physical education research. It is focused around the following study questions: (1) What are the most influential publications within the research field? (2) What are the research fronts in physical education studies?